Dumb and Forked: The Street Tree Poetics of Millay and Williams. Issue 1 (February 2021) - Daniel, Julia E.
Abstract : This urban ecocritical study reads the poetry of Edna St. Vincent Millay and William Carlos Williams in the context of the American street tree movement, a civic health and beautification program that advocated for the planting of shade trees along urban thoroughfares. It argues that both poets critique the 'ideal' street tree forwarded by the movement. In 'City Trees, ' Millay presents a shade tree whose therapeutic effects are overwhelmed by the noise pollution in New York City, much like the speaker herself. In 'Young Sycamore, ' Williams eschews the visual ideal of symmetrical, evenly-spaced shade trees in favor of a wily, asymmetrical organism that actively torques toward the light. By extension, these poets present city habitats as alternately more toxic and more wild than the street tree movement had imagined, a critique with ramifications for contemporary urban reforestation movements today.